Controlling P10 LED for Displaying Real Time Information of Time, Temperature & Humidity and Air Quality - praditra, falih rama; boediardjo, kirina; sinaga, maralo (Liaison Journal of Engineering, 2023)
The objectives of this thesis are to create a huge display for displaying various information inspired by automatic weather station. Date and time, temperature, humidity, and carbon monoxide data will be read using sensors often used in commercial applications and displayed so that people can see it even from a distance. People frequently disregard this information as unnecessary because they believe it is not required in everyday activities. With ESP32 as the controller connect to LED P10 as the display, generate a static text that inform any data that read by sensors is a straightforward process. Keywords: display, sensor, ESP32, LED, P10